The answer is C. 3, because you're essentially saying 9 - (3 × 2) and that is 9 - 6, which equals 3. I hope this helps!
Answer:
14256
Step-by-step explanation:
Find the Greatest Common Factor (GCF)
GCF = 2xy
Factor out the GCF. (Write the GCF first. Then, in parentheses, divide each term by the GCF.)
2xy(8x^3y/2xy + -8x^2y/2xy + -30xy/2xy)
Simplify each term in parenthesis
2xy(4x^2 - 4x - 15)
Split the second term in 4x^2 - 4x - 15 into two terms
2xy(4x^2 + 6x - 10x - 15)
Factor out common terms in the first two terms, then in the last two terms;
2xy(2x(2x + 3) -5(2x + 3))
Factor out the common term 2x + 3
<u>= 2xy(2x + 3)(2x - 5)</u>
A = $ 1,721.28
A = P + I where
P (principal) = $ 1,500.00
I (interest) = $ 221.28
Answer:
4^y = x + 3
2^y = x + 2
Step-by-step explanation:
log_4(x + 3 ) = log_2 (2 + x )
log_4( x + 3 ) = y
log_2 (2 + x ) = y
4^y = x + 3
2^y = x + 2